The Relationship Between Decision-making Capacity and the Domains of Awareness in Alzheimer Disease. (27th January 2022) - de Souza, Natalie A.P.; de Oliveira, Felipe; de Carvalho, Raquel L.S.; Dourado, Marcia C.N.
Abstract : People with Alzheimer dementia (PwAD) who are aware of their overall cognitive function and diagnosis are more likely to be judged competent in decision-making capacity. Therefore, we aimed to investigate the relationship between decision-making capacity and the different domains of awareness and the relationship between decision-making capacity and the cognitive and clinical impairment of the PwAD. Using a cross-sectional design, we included 121 PwAD and their caregivers. Awareness was assessed across domains, including cognitive functioning and health condition, functional activity impairments, emotional state, social functioning, and interpersonal relationships. The MacArthur Competence Assessment Tool for Treatment was adopted to gather information about decision-making abilities. We found that decision-making capacity is related to the cognitive and functional domains of awareness and relatively independent of the emotional functioning and the relationship domains. Our finding highlighted that PwAD who are unaware of the disease or the cognitive and functional impairments might be unlikely to appreciate the personal benefits of a proposed health treatment or to understand and judge the personal consequences of a decision accurately.